Functional traits provide evidence of land use transformations of Tucuman-Bolivian Forests at the catchment scale - Manco Rengifo, Yurani (2024)
Bolivia has one of the highest rates of deforestation in South America and is one of the countries with the highest frequency of forest fires worldwide, leading to a decrease in forest coverage and increased anthropogenic land pressure. The objective of this study was to characterize plant functional traits and determine their relationship with the landscape transformation of Tucuman-Bolivian Forests. A comparative study was designed by selecting three catchments with well-preserved natural vegetation and three transformed catchments for studying structural (height, diameter at breast height, canopy size, resprouting, and main branches) and foliar (leaf water content, leaf area, specific leaf area, stomatal density, and trichomes density) traits of vegetation, as well as community traits (epiphyte biomass and fine root density). Increased landscape fragmentation, augmented intraspecific trait variability, being more evident in foliar traits and species present in both types of catchments. Yet, structural traits were reduced (except resprouting) due to the replacement of species that arrive after the transformation, along with a decrease in light competition. In contrast, height of herbaceous species increased in transformed catchments, resulting from the anthropic selection of pastures from the Poaceae family for livestock. The vegetation of transformed catchments had lower stomatal density as a possible strategy to reducing water loss through transpiration. Also, lower epiphyte biomass was evidenced due to microclimatic changes devoid of canopy, particularly due to the reduction in air relative humidity and the increase in solar radiation.